2016
DOI: 10.1155/2016/1782835
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Perils of Extended Spectrumβ-Lactamase Producing Enterobacteriaceae Clinical Isolates in a Teaching Hospital of Nepal

Abstract: Introduction. Infections due to extended spectrum β-lactamase producing Enterobacteriaceae are on the rise. They pose serious public health problems due to their resistance to large number of antibiotics. However, little is known about the genotypes of ESBL from Nepal. Therefore, the study presents results of phenotypic and molecular characterization of ESBL producing Escherichia coli and Klebsiella spp. isolated from various clinical specimens in a tertiary care teaching hospital of Nepal. Methods. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
23
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 27 publications
17
23
6
Order By: Relevance
“…The data of ESBL producing K. pneumoniae in Nepal ranges from 18.4%-30.0% [27,28]. Our study showed higher percentage of ESBL (43.3%) than the previous studies from Nepal, however, was similar to data of another study from South East Asia (46.7%) [29].…”
Section: Discussionsupporting
confidence: 84%
“…The data of ESBL producing K. pneumoniae in Nepal ranges from 18.4%-30.0% [27,28]. Our study showed higher percentage of ESBL (43.3%) than the previous studies from Nepal, however, was similar to data of another study from South East Asia (46.7%) [29].…”
Section: Discussionsupporting
confidence: 84%
“…The incidence of ESBL producing E. coli among the outpatients (89.1%) was higher than inpatients (63.64%) which were in contrast to the ndings [43], which revealed that incidence of ESBL producing E. coli among the inpatients was higher than in outpatients. In this study, the ESBL producing E. was found comparatively higher in number than in the studies by Parajuli et al and Seyedjavadi et al [48,49]. Pokhrel et al, 2014, andChander andShrestha 2013 [44, 50] revealed even less ESBL producing E. coli.…”
Section: Discussioncontrasting
confidence: 50%
“…However, the bla-CTX-M gene has been described as the most common genotype of ESBL among enterobacteriaceae in several literatures [40][41][42]. In our previous report too, we found the dominance of the bla-CTX-M gene among ESBLproducing enterobacteriaceae from various clinical specimens [22]. Moreover, multiple occurrences of genes in a same organism were also noted, where bla-TEM + bla-CTX-M (54.8%) was common.…”
Section: Discussionmentioning
confidence: 51%
“…Polymerase chain reaction-(PCR-) based amplification of ESBL genes was carried out as the method previously described [22]. For instance, multiplex PCR was carried out to detect the plasmid genes for SHV and CTX-M, while conventional linear PCR was used for TEM-type ESBL genes.…”
Section: Plasmid Dna Extraction and Amplificationmentioning
confidence: 99%